Evolutionary trajectories of tooth histology patterns in modern sharks (Chondrichthyes, Elasmobranchii). Issue 5 (22nd December 2019) - Jambura, Patrick L.; Türtscher, Julia; Kindlimann, René; Metscher, Brian; Pfaff, Cathrin; Stumpf, Sebastian; Weber, Gerhard W.; Kriwet, Jürgen
Abstract: During their evolutionary history, modern sharks developed different tooth mineralization patterns that resulted in very distinct histological patterns of the tooth crown (histotypes). To date, three different tooth histotypes have been distinguished: (i) orthodont teeth, which have a central hollow pulp cavity in the crown, encapsulated by a prominent layer of dentine (orthodentine); (ii) pseudoosteodont teeth, which have their pulp cavities secondarily replaced by a dentinal core of porous dentine (osteodentine), encased by orthodentine; and (iii) osteodont teeth, which lack orthodentine and the whole tooth crown of which consists of osteodentine. The aim of the present study was to trace evolutionary trends of tooth mineralization patterns in modern sharks and to find evidence for the presence of phylogenetic or functional signals. High resolution micro‐computed tomography images were generated for the teeth of members of all nine extant shark orders and the putative stem group †Synechodontiformes, represented here by three taxa, to examine the tooth histology non‐destructively. Pseudoosteodonty is the predominant state among modern sharks and represents unambiguously the plesiomorphic condition. Orthodonty evolved several times independently in modern sharks, while the osteodont tooth histotype is only developed in lamniform sharks. The two shark orders Heterodontiformes and Pristiophoriformes showed highly modified tooth histologies, with Pristiophorus exhibiting a histology only known from batomorphs (i.e. rays and skates), and Heterodontus showing a histological difference between anterior and posterior teeth, indicating a link between its tooth morphology, histology and durophagous lifestyle. The tooth histotype concept has proven to be a useful tool to reflect links between histology, function and its taxonomic value for distinct taxa; however, a high degree of variation, especially in the pseudoosteodont tooth histotype, demonstrates that the current histotype concept is too simplistic to fully resolve these relationships. The vascularization pattern of the dentine might offer new future research pathways for better understanding functional and phylogenetic signals in the tooth histology of modern sharks. Abstract : Using micro‐computed tomography techniques, we examined the tooth mineralization in modern shark clades (Elasmobranchii, Chondrichthyes). The inclusion of fossil taxa and computing ancestral states allowed us to trace back the development of different mineralization patterns in deep time.